Mercury Emission and its Control in Chinese Coal-Fired Power Plants - Zhou, Jinsong; Luo, Zhongyang; Zhu, Yanqun; Fang, Mengxiang (Advanced Topics in Science and Technology in China, 2013)
"Mercury Emission and its Control in Chinese Coal-Fired Power Plants" focuses on investigating mercury emissions samplings and measurement in Chinese coal-fired power plants, mercury emission estimations and future trends, mercury speciation transformation during coal combustion, mercury control and mercury stability in byproducts. The book not only introduces mercury emissions from actual coal-fired power plants, but also presents studies on the mechanism of mercury emission and its control. This is a valuable reference for engineering thermal physicists, thermal engineers, and chemical engineers. Jinsong Zhou, Zhongyang Luo, and Mengxiang Fang are Professors in the College of Mechanical and Energy Engineering, Zhejiang University, China. Yanqun Zhu is Associate Professor in the College of Mechanical and Energy Engineering, Zhejiang University, China.